GREEN ECONOMY TRANSFORMATION: OPPORTUNITIES AND CHALLENGES IN THE TRANSPORT SECTOR FOR REDUCING THE IMPACTS OF CLIMATE CHANGE - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Green economy transformation in the transport sector is a crucial step to mitigate the impacts of climate change, as transport is a major contributor to greenhouse gas emissions. This involves shifting to electric vehicles, implementing renewable fuels and green technologies that can significantly reduce carbon emissions. Despite the promise of environmental and health benefits, this transformation faces major technological, economic, and social challenges, such as high costs, lack of infrastructure, and public resistance to change. Therefore, close collaboration between the government, private sector, and society is needed to overcome these obstacles. Green economy transformation, with the right policy support and investment in technology, can create opportunities for sustainable development in the transport sector and promote long-term economic and ecological balance.